Development of the Religious Values Model to Improve Learning Outcomes of the Digestive System Subject - Nurika, Nurika; Chandra, Edy; Mulyani, Asep (Scientiae educatia, 2021)
Islamic education values are crucially applied in learning biology because its topics are conceptual and contextual. Thus, biology class must prioritize the learning values. Teachers can use each design containing to develop learning activities. The values model is a learning model prioritizing the application of life values. This study aimed to examine the students’ activities in the experimental class, examine different learning outcomes between students applying the religious-based values learning model and students applying conventional learning models, and examine students' attitudes towards biology learning applying the values learning model. This research employed the development research design and test one experimental class in the broad test. The experimental and control classes with a purposive sampling technique were employed in the pretest-posttest control group research design. The data were collected using observation, tests, and questionnaires of attitude values. The data were analyzed using the SPSS V.21 Software. The results showed that student learning activities increased in each test. The N-Gain value signified that the experimental class had higher learning outcomes than the control class. In addition, the learning outcomes in each test increased. The experimental class of students who applied biology with the religious-based values model in each meeting increased. The experimental class had higher learning outcomes than the control class. The average posttest score of student attitude in the experimental class was 87.59, while in the control class was 81.38. Meanwhile, the experimental class had the average posttest score of the implementation test was 80.37, and the posttest control class was 79.44. The development of religious values models can improve student learning outcomes